Formulasi Romance dalam Beauty Case Karya Icha Rahmanti: Kajian Sastra Feminis - Tania Intan; Vincentia Tri Handayani Tri Handayani (Madah: Jurnal Bahasa dan Sastra, 2019)
This study aims to reveal the formulation of romance in chick lit Beauty Case (2005), the second work of Icha Rahmanti after Cintapuccino (2004). The methodological approach used is the study of feminist literature and structural analysis methods. Because chick lit always discusses women, the theoretical foundation of this research must be linked to women's perspectives, includes the ideas of Radway, Modlesky, Gill and Herdierckerhoff who were used to explore the narrative aspects of romance formulation, which included plots, characterization, and point of view. The results show that (1) although chick lit is a romance subgenre, the novel Beauty Case storyline does not follow the normative narrative standard of romance because there are changing plots. However, the end of the novel follows the romance formulation, which ends happily; (2) the main female figure in the novel does not really make a search for true love, but rather searches for identity. In addition, the portrayal of male characters also does not follow the formulation of romance that has exemplary characters; (3) the storyteller in this novel is the first single person, the main female figure, with an intimate, subjective, and limited nature of storytelling, according to the formulation of romance.